Real-time PCR 기술의 생물학적 폐수처리에서의 응용 - 엄호섭; 상병인; 이선미; 정윤철 (한국물환경학회, 2006)
About 99% of microorganisms in the environment are unculturable. However, advances in molecular biology techniques allow for the analysis of living microorganisms in the environment without any cultivation. With the advent of new technologies and the optimization of previous methods, various approaches to studying the analysis of living microorganisms in the environment are expanding the field of microbiology and molecular biology. In particular, real-time PCR provides methods for detecting and quantifying microorganisms in the environment. Through the use of the methods, researchers can study the influence of environmental factors such as nutrients, oxygen status, pH, pollutants, agro-chemicals, moisture and temperature on the performances of environmental processes and some of the mechanisms involved in the responses of cells to their environment. This review will also address information gaps in the analysis of the microorganisms using real-time PCR in the environmental process and possible future research to develop an understanding of microbial activities in the environment.